A 3.7 kW on-board charger based on modular circuit design - Schmenger, Jens; Zeltner, Stefan; Kramer, Reinhard; Endres, Stefan; März, Martin (IECON 2015 - 41st Annual Conference of the IEEE Industrial Electronics Society, 2015)
In this paper a 3.7 kW On-board charger (OBC) for electric or plug-in hybrid vehicles is proposed. With regard to standardization, cost reduction and to increase the volume of produced devices, the OBC is derived from a fully modular circuit and control structure. The two-stage circuit arrangement consists of an isolated full bridge ZVS resonant converter and an interleaved boost converter for power factor correction (PFC). The proposed charger has a volume of less than 4 liters and a weight of 3 kg. The experimental result indicates an efficiency of more than 95 percent over the full battery voltage range at an input voltage of 230 Vac. The output voltage for full load and best efficiency varies from 315-395 V.
CRIS-Team Scopus Importer:2023-03-07
Keywords: battery charger; electric vehicle; energry storage system; plug-in; power electronics converters